Peran Fasilitator Pendamping Pada Implementasi Program Bestee Kepada Nasabah BTPN Syariah MMS Jogoroto Jombang - Melfiya Rosita; Perdana, Putra; Huda, Syamsul (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Bank BTPN Syariah provides various financing products and services and opens access to financial services for productive underprivileged women to obtain business capital, as well as providing training and mentoring. Bank BTPN Syariah continues to collaborate with various parties including students through the "Bestee Contributor" internship program through the Merdeka Campus Certified Independent Study and Internship (MSIB). This research aims to determine the role of accompanying facilitators in implementing the bestee program for BTPN Syariah customers at MMS Jogoroto Jombang. The method used by the author is a qualitative method with a descriptive approach. With this assistance program, it provides crucial benefits for customers. Among them, the income, skills and insight of BTPN Syariah customers have increased, because they have implemented the material provided by the accompanying facilitator. The accompanying facilitator has been successful in carrying out his role, namely providing provision, knowledge and skills in entrepreneurship to customers, so that the hard skills and soft skills of BTPN Syariah customers at MMS Jogoroto Jombang can be formed.